Digital competence using the example of executives in residential care facilities in Germany—a comparison - Liebl, Stefanie; Tischendorf, Tim; Hummel, Michel; Günther, Lydia; Schaal, Tom (Frontiers in Health Services, 2024)
field of professional care and the associated increasing demands on the skills of nursing staff. The European Union considers digital skills to be one of the eight key competences for lifelong learning. At present, few reliable statements can be made about the status of digital skills in professional nursing care in Germany. The aim of this study was to map the current status of digital competences of executives in full inpatient care facilities in Germany and to identify possible differences to reference values of academics. Methodology: This survey is based on a Germany-wide cross-sectional survey in full inpatient care facilities (N = 8,727). The survey instrument Digital Competences Framework (DigComp 2.2) according to the European Union's reference framework was used as the basis for recording the digital competence characteristics. The statistical analysis was descriptive and inferential (t-test, two-sided, p<0.05). Results: Out of 15 items across five dimensions, significant differences for nine items can be determined. The competence levels of the participating managers from the full inpatient care facilities were lower compared to the reference sample. Discussion: In order to be able to counter the skills discrepancy shown by the study in the future, it is of central importance to deepen knowledge and skills in the area of digitalization in the care context.